WHEN FOREIGN LANGUAGE SPELLS CONFLICT IN THE BRAIN: THE USE OF ENGLISH IN THE ISLAMIC BOARDING SCHOOL IN INDONESIA - Siswoyo, Siswoyo; Fitri Wulandari; Fatma Yuniarti (Universitas Negeri Surabaya, 2024)
English, a foreign language used as an everyday conversation in the Islamic boarding school, has created new language conflict in the brain. This article explores the language conflicts experienced by students when producing English. The data of this article taken from in-depth interviews with thirty senior Islamic high school students. This research shows that language competition in the brain has created language conflict. This article’s main limitation is that it relies solely on students' perspectives from the lower motivation and does not consider the whole level of the students. Further research, thus, should use a more comprehensive approach that integrates a view of the entire students’ level, thereby enabling it to formulate a more comprehensive solution.